Determinants of Noncommunicable Disease Prevention Behaviors: The Roles of Health Literacy, Self-Efficacy, and Social Support - Habibi; Abubakar Betan (Jurnal Ilmu Kesehatan Nusantara, 2025)
Background: Noncommunicable diseases remain a major public health challenge, although many risk factors can be reduced through consistent preventive behaviours. Health literacy, self-efficacy, and social support may determine individuals’ capacity to adopt and maintain healthy lifestyles. Research Objective: This study examined the roles of health literacy, self-efficacy, and social support as determinants of noncommunicable disease prevention behaviours among adults in Makassar, Indonesia. Methods: A quantitative cross-sectional study involved 200 adults selected through multistage random sampling. Data were collected using validated questionnaires and analysed using descriptive statistics, Pearson correlation, and multiple linear regression at a significance level of p<0.05. Results: Good prevention behaviour was identified in 51.0% of respondents. Health literacy (r=0.574), self-efficacy (r=0.612), and social support (r=0.486) were positively correlated with prevention behaviour (all p<0.001). Multiple linear regression showed that self-efficacy was the strongest determinant (β=0.356), followed by health literacy (β=0.302) and social support (β=0.218). The model explained 52.9% of the variance in prevention behaviour. Conclusion: Stronger self-efficacy, adequate health literacy, and supportive social environments promote better noncommunicable disease prevention behaviours. Community programmes should integrate health education, behavioural empowerment, family support, and accessible periodic screening within diverse urban community settings and primary healthcare services.